A Glance into the Tunnel: Experimental Evidence of Expectations Versus Comparison Considerations - Harald Lang; Kai A. Konrad; Florian Morath (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Learning that others earn more may reduce individual well-being but can also be informative about the own income prospects. This paper provides experimental evidence that separates direct effects of income comparisons on well-being and informational effects from observing changes in the income of others. In an environment of uncertainty about the own income we find that both the direct comparison effects and the informational effects are asymmetric. Individual beliefs about the own income are adjusted downwards when observing that others are likely to earn less but do not change significantly when observing that others are likely to earn more. Individual satisfaction decreases when observing that others are likely to earn more but does not change significantly when observing that others are likely to earn less. Overall, individuals are more reactive to bad news than to good news .
Keywords: C91; D31; D84; 330